(untitled) (Politeja, 2024)
THE CZECH REPUBLIC IN THE EUROPEAN UNION: 20 YEARS OF MEMBERSHIP IN THE EYES OF THE CZECH SOCIETY The Czech Republic has been a member of the European Union since 2004. Accession was decided by the country’s citizens in a referendum in 2003, with more than 77% of voters approving of this move in international politics. Over time, the Czech public’s assessment of the European Union and its actions has become increasingly critical, which has become apparent in opinion polls. The number of those dissatisfied with the functioning of the EU at the turn of the first decade even exceeded the number of those satisfied. The Czechs were positive about the EU’s environmental, security or cultural activities, while they were negative about the euro and its possible introduction from around 2009. The reasons for this can be traced to important international events that were also noticeable in the Czech Republic (financial crisis of 2008-2010, migration crisis, COVID-19 pandemic). A feature of the country is also the relatively sceptical attitude of political parties towards European integration, which was also significant.